Principles of green chemistry: building a sustainable future - Fatma Kurul; Beyzanur Doruk; Seda Nur Topkaya (Discover Chemistry)
Abstract Green chemistry is an interdisciplinary field that focuses on minimizing hazardous substances and promoting sustainable alternatives in chemical processes to conventional chemical processes and products. This review provides a comprehensive analysis of the fundamental principles, historical development, and practical applications of green chemistry with a particular emphasis on its role in advancing sustainable chemical synthesis, analytical methodologies, and industrial practices. Originating from the environmental activism of the 1960 s inspired by Rachel Carson's"Silent Spring,"green chemistry was formally established in the 1990 s through the 12 principles set by Paul Anastas and John C. Warner. These principles emphasize waste prevention, atomic economy, reducing hazardous chemicals, and using renewable raw materials. Green chemistry significantly impacts sectors such as pharmaceuticals, cosmetics, and education. In the pharmaceutical industry, it fosters environmentally safer analytical methods. The cosmetics sector benefits from biodegradable materials, while educational institutions implement sustainable waste management and laboratory practices. International conferences and academic publications have advanced global awareness of green chemistry, promoting sustainability goals like reducing environmental impacts, optimizing resource use, and minimizing waste. A key focus of this study is the green synthesis of nanoparticles which has emerged as a sustainable alternative to traditional synthesis methods that often rely on toxic reagents Plant-derived biomolecules serve as reducing and stabilizing agents in the synthesis of silver nanoparticles (AgNPs). These eco-friendly approaches eliminate the hazardous chemicals while yielding biocompatible nanoparticles with enhanced antimicrobial and catalytic properties, demonstrating their potential in nanotechnology and biomedical applications. Additionally, green analytical chemistry has revolutionized chemical monitoring by implementing solvent-free methodologies, real-time pollution tracking, and waste minimization techniques. The integration of green chemistry into academic and industrial settings has played a critical role in addressing global challenges such as environmental pollution, climate change, and resource depletion. This review highlights the necessity of widespread adoption of green chemistry principles to ensure economic sustainability, regulatory compliance, and scientific innovation. Future research should focus on optimizing green synthetic techniques, addressing scalability challenges, and fostering interdisciplinary collaboration to accelerate the transition toward a more sustainable future. Graphical abstract